2013
DOI: 10.1186/1556-276x-8-382
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of well-dispersed CdS nanocrystals in semiconducting polymers

Abstract: A straight synthetic route to fabricate hybrid nanocomposite films of well-dispersed CdS nanocrystals (NCs) in poly[2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) is reported. A soluble cadmium complex [Cd(SBz)2]2·MI, obtained by incorporating a Lewis base (1-methylimidazole, MI) on the cadmium bis(benzyl)thiol, is used as starting reagent in an in situ thermolytic process. CdS NCs with spherical shape nucleate and grow well below 200°C in a relatively short time (30 min). Photoluminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…CO +2 -doped CdS/ polyvinyl pyrolidone composite was synthesized by chemical precipitation method [44]. Spin-coating technique was used to prepare thin films of CdS/poly[2-methoxy-5-(2′ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) nanocomposite [45]. Several other CdS/polymer nano composites such as CdS/polyamidoamine dendrimer [46], CdS/ poly[4-(n-acryloyloxyalkoxy)benzoic acid] [47], and many more [48,49] were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CO +2 -doped CdS/ polyvinyl pyrolidone composite was synthesized by chemical precipitation method [44]. Spin-coating technique was used to prepare thin films of CdS/poly[2-methoxy-5-(2′ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) nanocomposite [45]. Several other CdS/polymer nano composites such as CdS/polyamidoamine dendrimer [46], CdS/ poly[4-(n-acryloyloxyalkoxy)benzoic acid] [47], and many more [48,49] were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…17 This polysaccharide was already used as an environment for controlled growth of II-VI semiconductors, 18 Co, Ni, and CoNi nanoparticles, 19 iron oxide nanostructures 20 as well as antimicrobial ZnO nanoparticles 21,22 and hybrid ZnO/Ag nanocubes. 23 However, to the best of our knowledge, alginates were not used for the preparation of diluted magnetic semiconductor nanoparticles such as the CdS:Mn described in the present work. In this study, we used an in situ chemical synthesis for the preparation of CdS:Mnalginate nanocomposites in which the nanoparticles were formed directly within the biopolymer matrix.…”
Section: Introductionmentioning
confidence: 94%
“…MEH-PPV/ PbS composites were prepared by Watt et al 9 via directly growing PbS nanocrystals in MEH-PPV solution without surfactants; they showed that the polymer chains could act as templates to stabilize nanocrystal growth in solution. The growth of well-dispersed CdS nanocrystals in MEH-PPV was reported by Laera et al 16 via a soluble cadmium complex [Cd(SBz) 2 ] 2 •MI used as starting reagent in an in-situ thermolytic process. To further enhance the photoelectric conversion efficiency of the product, we synthesized a phosphonic ester end-functionalized P3HT, which could afford more intimate contact with the nanocomposites by ionic bonds, which is a powerful chemical bond, between Cd 2+ ions and phosphate.…”
Section: Introductionmentioning
confidence: 97%
“…However, the presence of surfactants severely reduces the device efficiency by impeding the transfer of charge between nanocrystals and polymer, as well as the transport of electrons between adjacent nanocrystals 15 . Recently, there have been some reports 4,9,16 of the direct synthesis of semiconductor nanocrystal/ conjugated polymer composites with the connection of covalent bond. By such a new approach, the negative effects of the surfactants to charge transfer are no need to consider.…”
Section: Introductionmentioning
confidence: 99%